Increased liver carcinogenesis and enrichment of stem cell properties in livers of Dickkopf 2 (Dkk2) deleted mice - Maass, Thorsten; Marquardt, Jens; Lee, Ju-Seog; Krupp, Markus; Scholz-Kreisel, Peter; Mogler, Carolin; Schirmacher, Peter; Müller, Martina; Westphal, Heiner; Galle, Peter R.; Teufel, Andreas (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.3293 Thorsten Maass, Jens Marquardt, Ju-Seog Lee, Markus Krupp, Peter Scholz-Kreisel, Carolin Mogler, Peter Schirmacher, Martina Müller, Heiner Westphal, Peter R....
Published: March 16, 2015
Gesehen am 22.05.2020